Gaya Bahasa dalam Lirik Lagu Berbahasa Jawa Berjudul Lestari: Kajian Stilistika - Nanda Nursa Alya; Haryo Untoro (STIKes Ibnu Sina Ajibarang, 2024)
Javanese literature in the form of songs is currently favored by people in Indonesia. One of these songs is Lestari. Lestari contains the theme of love and admiration for a woman. The theme is presented with lyrics that contain language styles. The formulation of this research problem is how the use of language styles in the lyrics of the song 'Lestari'. This study aims to analyze the use of language style in the lyrics of the song 'Lestari'. The theory used is language style by Gorys Keraf. The methods used are data collection, data analysis and classification of language styles, and presentation. The data source comes from the Youtube channel Khatulistiwa Record which is transcribed independently. The results show that the song lyrics contain rhetorical language styles in the form of alliteration, assonance and hyperbole, as well as figurative language styles including metaphor and simile.